The Effectiveness of Using Audio Visual Media Toward Students’ Listening Skill at Eleventh Grade SMA N 9 Jambi - Eroza, Aprilia; Fitri, Nurul; Aisyah, Siti (Universitas Batanghari Jambi, 2023)
Listening skills are techniques that contribute to the ability to absorb information accurately when communicating with others. This type of research was a quasi-experimental study of 133 people. Through a simple random selection procedure, 36 XI IPS 3 students were selected for the control class and 33 XI IPS 1 students were selected for the experimental class. A technique for collecting data by distributing questions to respondents. In this research, the data analysis technique used the Statistical Package for the Social Sciences (SPSS) version 21 for Windows. The results of this research showed that, (1) Students' listening skills in English subjects taught using audio-visual media have an average arithmetic score of 80,44, (2) The average listening skill of students in English subjects taught only by listening media (speakers) was 77,31, (3) Students’ Listening skills in English subjects taught using the audio-visual media were higher than students’ Listening skills in English subjects taught using listening audio (speaker), with a value of Sig. 0.000 < 0.05. The results showed that English students experienced a significant effect in listening skills after learning by video.